Evaluation of hepatic 11 beta-hydroxysteroid dehydrogenase activity by cortisone acetate test in young adults with diabetes mellitus type 1 - Šimůnková, K; Hampl, R; Hill, M; Kříž, L; Vrbíková, J; Kvasničková, H; Vondra, K (Physiological research, 2011)
Cortisone acetate test was performed in twelve young adult patients with diabetes mellitus type 1, after dexamethasone administration to suppress endogenous cortisol production. Previous screening revealed that all of the subjects had peak cortisol responses in the range from subnormal to normal, as determined by a low-dose Synacthen test. The aim was to find out whether these patients would exhibit different conversion of cortisone to cortisol by 11beta-hydroxysteroid dehydrogenase. Using multifactorial ANOVA the following significant relationships were obtained between cortisol or cortisol/cortisone ratio measured during the test and other parameters examined a) before dexamethasone suppression and b) during the test: a) Cortisol at 120(th) minute negatively correlated with daily insulin dose and positively with basal aldosterone. Cortisol/cortisone ratio at 60(th), 120(th), 180(th), and 240(th) minute negatively correlated with basal aldosterone/plasma renin activity ratio, urinary free cortisol/24 hours and positively with basal dehydroepindrosterone sulphate. b) Cortisol at 120(th) minute negatively correlated with suppressed basal serum glycemia; cortisol/cortisone ratio during the whole test negatively correlated with supressed basal ACTH. The examination of peripheral metabolism of cortisol using cortisone acetate test in patients with diabetes mellitus type 1 showed adaptive changes of 11beta-hydroxysteroid dehydrogenace activity associated with altered cortisol tissue supply.
Keywords: játra; dexamethason; Cortisone; Humans; renin; Hydrocortisone; hydrokortison; 11-beta-hydroxysteroiddehydrogenasy; Female; dospělí; dehydroepiandrosteronsulfát; Dehydroepiandrosterone Sulfate; lidé; Renin; diabetes mellitus 1. typu; Adult; ženské pohlaví; Liver; Male; Insulin; Dexamethasone; aldosteron; inzulin; Aldosterone; kortison; mužské pohlaví; Diabetes Mellitus, Type 1; 11-beta-Hydroxysteroid Dehydrogenases